Recent Advances in Thianthrenation/Phenoxathiination Enabled Site-Selective Functionalization of Arenes - Chen, Xiao-Yue; Wu, Yichen; Wang, Peng (Synthesis, 2022)
Site-selective functionalization of simple arenes remains a paramount challenge due to the similarity of multiple C–H bonds in the same molecule with similar steric environment and electronic properties. Recently, the site-selective thianthrenation/phenoxathiination of arenes has become an attractive solution to reach this challenging goal and it has been applied in the late-stage functionalization of various bioactive molecules. This short review aims to summarize recent advances in the site-selective C–H functionalization of arenes via aryl thianthrenium salts, as well as mechanistic insights in the remarkable site-selectivity obtained in thianthrenation step.1 Introduction2 Site-Selective Thianthrenation of Arenes and Mechanistic Insight3 Thianthrenation-Enabled Site-Selective Functionalization of Arenes3.1 Thianthrenation-Enabled C(sp2)–C Bond Formation Reaction3.2 Thianthrenation-Enabled C(sp2)–X Bond Formation Reaction4 Conclusion and Outlook
Keywords: thianthrenation; phenoxathiination; arene; sulfonium salts; C–H functionalization